Impementasi Media Pembelajaran Berbasis Animasi 3D Menggunakan Aplikasi Plotagon Studio Pada Materi Pergerakan Organisasi Menuju Kemerdekaan di SMP Cendana DDI Samarinda - Hendi Sopian; Muhamad Sopyan (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research discusses the impact of using 3D animation, especially using the Plotagon Studio application, on material on organizational movement towards independence at Cendana DDI Samarinda Middle School, which has several objectives: 1) To find out the procedures for implementing learning with 3D animation using the Plotagon Studio application. 2) to find out how teachers and students respond to learning using 3D animation, especially with the Plotagon Studio application at SMP Cendana DDI Samarinda. The type of research used is qualitative descriptive research which includes data collection, data reduction, data presentation, and drawing conclusions. The results of this research reveal that when using the Plotagon Studio application there are several procedures that need to be carried out. Apart from that, there were responses obtained from teachers and students regarding the use of 3D animation videos and the use of the Plotagon Studio application at SMP Cendana DDI Samarinda.